Analysing the Concept of Derogation in Regional and Continental Integration: A Case of Zimbabwe - Binha, Oswell; Mwakurudza, Kudzanai (New Innovations in Economics, Business and Management Vol. 2, 2021)
Like any other continent, Africa has embraced continental integration to create continental economies of scale in pursuit of sustainable economic growth and development. The notion of resource pooling, collaborative capacity development, complementary management of resource endowments, and internal markets will provide an opportunity to create a robust African economy capable of overcoming poverty, unemployment, and social distress. The African development architecture, as created by the founding nationalists, neglects the concept of continental collective capacity development for shared economic performance, enhanced and simplified movement of persons and goods, development of common regional infrastructure, promotion of conducive macroeconomic environment favourable to the facilitation of economic development amongst African states. The recent realisation by Pan-African Institutions that deeper intra Africa collaboration is possible beyond matters of continental peace and security to engendering macroeconomic convergence is a departure from the usual rhetoric of national sovereignty. Research has shown that 80 cents out of every dollar made in Africa are a result of trade. The realisation that continental integration remains a logical option came about against a background of efforts to railroad other multi-lateral arrangements with Africa, particularly on raw material trade. Progress has been made in creating African regional trade blocs, albeit with inherent constraints primarily driven by turfism, historical colonial attachments, a leadership gap and general institutional weaknesses in member-states. However, the general failure of rules-based economic engagements in Africa is of grave concern, militating against vast potential Africa has to increase intra African trade. This paper shall cross-examine and engage in an in-depth analysis on the concept of Derogation in Integration, putting into perspective Zimbabwe's derogation experiences in SADC, COMESA and the CFTA, whilst making comparative scrutiny with cases in other continents. Derogation by nature impacts the country seeking the Derogation and retards progress with the group committed to the cause of the economic cooperation. Zimbabwe falls in the same category and risks other countries invoking reciprocity to counter the effects of bad domestic economic policy.